P085: What do community paramedics assess? An environmental scan and content analysis of patient assessment in community paramedicine. (May 2019) - Leyenaar, M.; McLeod, B.; Penhearow, S.; Strum, R.; Brydges, M.; Brousseau, A.; Mercier, E.; Besserer, F.; Agarwal, G.; Tavares, W.; Costa, A.
Abstract : Introduction : Patient assessment is a fundamental feature of non-emergency community paramedicine (CP) home visit programs. In the absence of a recognized standard for CP assessment, current assessment practices in CP programs are unknown. Without knowing what community paramedics are assessing, it is difficult to ascertain what should be included in patient care plans, whether interventions are beneficial, or whether paramedics are meeting program objectives. Our objective was to summarize the content of assessment instruments used in CP programs in order to describe the state of current practice.Methods : We performed an environmental scan of all CP programs in Ontario, Canada, and employed content analysis to describe current assessment practices in CP home visit programs. The International Classification on Functioning, Disability, and Health (ICF) was used to categorize and compare assessments. Each item within each assessment form was classified according to the ICF taxonomy. Findings were compared at the domain and sub-domain of the ICF.Results : Of 54 paramedic services in Ontario, 43 responded to our request for information. Of 24 services with CP home visit programs, 18 provided their intake assessment forms for content analysis. Assessment forms contained between 13 and 252 assessment items (median 116.5, IQR 134.5). Overall, most assessments included some content from each of the domains outlined in the ICF, including: Impairments of Body Functions, Impairments of Body Structures, Activity Limitation and Participation, and Environmental Factors. At the sub-domain level, only assessment of Impairments of the Functions of the Cardiovascular, Haematological, Immunological and Respiratory systems appeared in all assessments. Few CP home visit program assessments covered most ICF sub-domain categories and many items classified to specific categories were included in only a few assessments.Conclusion : CP home visit programs complete multi-domain assessments as part of patient intake. The content of CP assessments varied across Ontario, which suggests that care planning and resources may not be consistent. Current work on practice guidelines and paramedic training can build from descriptions of assessment practices to improve quality of care and patient safety. By identifying what community paramedics assess, evaluation of the quality of CP home visit programs and their ability to meet program objectives can be improved and benchmarks in patient care can be established.